Birds of a feather flock together: Using trait-groups to understand the effect of macropod grazing on birds in grassy habitats. (February 2016) - Howland, Brett W.A.; Stojanovic, Dejan; Gordon, Iain J.; Radford, Jim; Manning, Adrian D.; Lindenmayer, David B.
Abstract: Restoration of appropriate disturbance regimes is a high conservation priority. However, for most species, little is known about appropriate disturbance regimes to achieve defined conservation outcomes. In this context, trait-based approaches can offer a means to generalize responses to environmental change across multiple species. Here, we investigated the potential of a trait-based approach to predict the preference of birds utilizing the grassy layers for different levels of grazing by a native grazer within grassy habitats in south-eastern Australia. We tested three hypotheses: 1) birds with particular traits (i.e. large ground-foraging, small ground-foraging, aerial insectivore, and ground-nesting/concealment) will show preferences for certain levels of grazing: 2) species within the same trait group will show preferences for a similar level of grazing intensity: and 3) different bird trait groups will favor different grazing intensities Overall, we found a significant relationship between grazing intensity and the richness of aerial insectivore and large ground-foraging trait groups utilizing the grassy layer, but not for the richness of small ground-foraging and ground-nesting/concealment trait groups. We also found that the likelihood of 3/3 aerial insectivores, 4/7 large ground-foragers, 3/10 small ground-foragers, and 1/3 ground-nesting/concealment species using the grassy layer was significantly related to grazing intensity. However, we found no significant relationship between the probability of 12 species using the grassy layer and grazing intensity, with other environmental factors potentially masking grazing response. Importantly, species within the same trait group showed a preference for similar grazing intensities, and different trait groups showed preference for different grazing intensities. For example, aerial insectivores, and a single ground-nesting/concealment species were more likely to use the grassy layer at lower grazing intensities, whereas large ground-foraging birds and small ground-foraging birds were more likely to use the grassy layer at higher grazing intensities. To maintain optimal grass structure for birds with varying grass structure preferences, landscapes should contain a heterogeneous mosaic of grazing intensities. Highlights: We modeled the response of 22 bird species belonging to three trait groups (aerial insectivore, ground-foraging, ground-nesting/concealment) to changes in grazing intensity. Different bird trait groups favored different levels of grazing. We need to ensure that the landscape contains a mosaic of grazing intensities. Intervention may be required to restore appropriate grazing patterns.